2019
DOI: 10.1016/j.heliyon.2019.e02080
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy-multidimensional deep learning for efficient prediction of patient response to antiretroviral therapy

Abstract: Drug component interactions are most likely to trigger unexpected pharmacological effects with unknown causal mechanisms, hence, demanding the discovery of patterns to establish suitable and effective regimens. This paper proposes a novel framework that embeds machine learning (ML) and multidimensional scaling (MDS) techniques, for efficient prediction of patient response to antiretroviral therapy (ART). To achieve this, experiment databases were created from two independent sources: a publicly available HIV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…The scoping review identified many studies that developed or validated models to predict therapeutic response for which prevention of ADEs in patients not expected to benefit from treatment was stated as a motivation for model development. 18 (27%) of 67 studies addressed this use case [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and focused on antineoplastics to treat patients with cancer (four [22%] of 18 studies), or antivirals with or without immuno modulators to treat patients with HIV or hepatitis C (five [28%]). Eight (44%) of 18 studies evaluated a single AI model.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review identified many studies that developed or validated models to predict therapeutic response for which prevention of ADEs in patients not expected to benefit from treatment was stated as a motivation for model development. 18 (27%) of 67 studies addressed this use case [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and focused on antineoplastics to treat patients with cancer (four [22%] of 18 studies), or antivirals with or without immuno modulators to treat patients with HIV or hepatitis C (five [28%]). Eight (44%) of 18 studies evaluated a single AI model.…”
Section: Reviewmentioning
confidence: 99%
“…Eight (44%) of 18 studies evaluated a single AI model. 47,49,51,[56][57][58]60,61 The remaining studies compared multiple models; use of support vector machines or tree-based algorithms generally resulted in the most favourable performance.…”
Section: Reviewmentioning
confidence: 99%
“…However, these integrated data sources are characterized by high volume and variation, and there are several data analytic challenges in the integrated data structure, including mismatched time scales and multilevel risk predictors. The recent developments in Big Data analytics, such as artificial neural network [ 50 , 51 ], LSTM Neural Network, random forest [ 51 , 52 ], support vector machine [ 51 ], and deep learning approach such as CNN [ 53 ], make it feasible to address these methodological challenges and predict virologic outcomes using data from multiple domains.…”
Section: Discussionmentioning
confidence: 99%
“… Muchas investigaciones biomédicas se ven claramente beneficiadas por la IA, ya que su aplicación genera una reducción en los costes y facilita la obtención y gestión de datos a través de modelos semánticos y relaciones entre variables desde una perspectiva diferente a la de la estadística clásica. La lógica difusa se está aplicando a investigaciones dentro del ámbito de la salud y está aportando nuevas visiones en el campo de creación de modelos de expansión de enfermedades infecciosas 45 , sistemas expertos para el diagnóstico 46 o respuestas a tratamientos 47 . …”
Section: Aplicaciones En Medicinaunclassified